A PERSPECTIVA MERCADÓFILA DO PLANEJAMENTO URBANO: UM ESTUDO SOBRE A PROMOÇÃO DA ESPECULAÇÃO IMOBILIÁRIA PELO PODER PÚBLICO MUNICIPAL – O CASO DE PONTA GROSSA/PR - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2012)
This study seeks to understand how the government of the city of Ponta Grossa - PR, through town planning legislation, seeks to shape the urban space, and indirectly lead to the creation of privileged spaces of real estate speculation, given its position adjusted to the interests market. Thus, we evaluated the historical factors of political culture prevailing in Ponta Grossa, zoning structure at different times, the changes produced by these in horizontal and vertical densities of urban space, as well as the implementation and effectiveness of the instruments of the “Estatuto da Cidade” to curb speculation in the current Master Plan. It was found that since the early days the city is dominated by a farmer elite, composed of farmers livestock owners of large properties. It was noted that zoning laws express a conservative mentality by providing only the traditional functional areas and not advance in its essence exclusionary. The Master Plans of the past stimulated the formation of a city scattered and sparse, and the current, while incorporating new tools to combat speculation brought by the “Estatuto da Cidade”, it uses the stratagem of not doing self-administered, allowing the maintenance of a market-enthusiastic planning, in other words, without any control or discipline of the market in favor of the social function of the city and property.
THE MARKET-ENTHUSIASTIC PERSPECTIVE OF URBAN PLANNING:A STUDY ON THE PROMOTION OF SPECULATION BUILDING BY PUBLIC MUNICIPAL POWER - THE CASE OF PONTA GROSSA/PR
Keywords: Planejamento Urbano; Especulação Imobiliária; Plano Diretor; Ponta Grossa/PR; Urban Planning; real estate speculation; Master Plan; Ponta Grossa/PR; CNPQ::CIENCIAS HUMANAS